SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PERSEDIAAN BERAS PADA KILANG PADI DT. AA DENGAN METODE FORECASTING - Jusin Jusin; Sri Wardani (UNIVERSITAS PELITA HARAPAN, 2019)
The DT.AA rice refinery company is a rice supply company. The company has difficulty in predicting the supply of rice that must be provided to meet customer needs, because the system used by the company is still traditional, namely by recording in books. To help the company in making predictions of rice supply, a decision support system was created to determine the amount of rice that the company must provide in meeting customer needs. In determining the rice supply, there are predetermined criteria: sales last 3 days to the last 7 days. So that the process of determining the supply of rice can run, we need a decision support system using the moving average method. Moving average methods are often known as moving averages. The system development method used in this research is the Rapid Application Development (RAD) method, system modeling using Unified Modeling Language (UML), HTML and PHP used as the programming language with the mySQL database system. With this decision support system that uses the forecasting method, can help companies in determining the rice supply that must be provided in meeting customer needs.